SELF-DRIVE TOURISM ROUTE IN LANGKAWI: AN APPLICATION OF CAPACITATED MULTIPLE TRAVELING SALESMAN MODEL - Zakiah Hashim; Wan Rosmanira Ismail (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This paper deals with the determination of the best possible route for self-drive tourism in Langkawi Island, Kedah. Self-drive tourism represents a type of tourism where tourists driving their own or rented car as the primary mode of transport and only involves a tourist destination which can be linked with a roads network. This study was applied the capacitated multiple traveling salesman problem (CMTSP) model to find the best possible self-drive tourism route that minimizes the total travel distance. There are 19 most attractive tourist destinations around Langkawi were considered in this study. The model has been solved using LINGO12.0 software. The results showed that tourist need to spend four days to visit all 19 tourist destinations around Langkawi with the minimum travel distance of 219.75 km. When the travel distance minimum, it also minimizes the travel (petrol) cost.